Analisis Gaya Komunikasi Konten Video TikTok @sadampermanawiyana dalam Membentuk Respon Audiens - Nadya Rizky Syarief; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study examines the communication style employed by TikTok content creator @sadampermanawiyana and its impact on audience responses. The research is grounded in the phenomenon of the growing role of content creators on TikTok in shaping public opinion and interaction. Utilizing a descriptive qualitative approach, data were collected through in-depth interviews with one expert informant, three active users, and one passive user. The results reveal that the creator employs a combination of relaxed, precise, dramatic, impression-leaving, open, and friendly styles, packaged in an informative storytelling format using semi-formal language. Audience responses encompass cognitive (understanding), affective (feelings), and conative (action) dimensions. These findings indicate that a flexible communication style tailored to the characteristics of the young audience on TikTok is a determining factor in the effectiveness of digital communication. The study underscores the importance of content creators selecting the appropriate communication style to foster meaningful audience interaction and engagement.